THE PECULIARITIES OF STORAGE OF MUSEUM OBJECTS - Kuryazova Darmonjon; Khamidova Dilfuza (Galaxy International Interdisciplinary Research Journal, 2021)
The aim of this work is to study the peculiarities of the preservation of museum objects. It studied the problems of preservation of museum objects, the chemical and physical properties of the exhibits, the methods used to slow down the process of obsolescence of objects. Conclusions were given on the solution of the problems indicated by the author.